'n Bio-ekologiese en gedragstudie van die jagluiperd Acinonyx jubatus jubatus (Schreber, 1776) (Afrikaans) - Eloff, F.C. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2007.